(untitled) (Journal of Science Foundation, 2019)
Background: Pelvic Inflammatory disease is a very common gynaecological condition among the women. Objectives: The purpose of the present study was to see the obstetrics factors related with the pelvic inflammatory disease. Methodology: This cross-sectional study was carried out in the Department of Obstetrics and Gynaecology at Dhaka Medical College Hospital, Dhaka, Bangladesh from November 2001 to April 2002 during the period of six (06) months and December 2002 to February 2003 for three (03) months with the total duration of nine (09) months. Women in child bearing age who were suffering from chronic pelvic inflammatory disease (PID) attended at the OPD of gynecology Department at Dhaka Medical College Hospital, Dhaka, Bangladesh were selected as study population. Relevant data from each patient were recorded in a questionnaire. Result: A total number of 150 cases were studied. Out of 146 patients 75.3% were delivered at home, 8.2% at hospital and 16.4% cases had their deliveries at home and at hospital also. Out of 146 patients 63.0% were delivered by untrained birth attendants at home and 36.99% were delivered by trained birth attendants. Out of 146 patients 54.1% had history of puerperal sepsis. However, the rest of the 67(45.9%) cases were normal puerperium. In this study 84.0% patients had history of MR, 18 percent had spontaneous abortion and 4.7 percent had induced abortion. Out of these 115 patients with history of pregnancy termination, 47.3% patients had history of pelvic infection following that event. Also, 2.7% gave history of ectopic pregnancy. Conclusion: In conclusion most of the PID patients are delivered at home with untrained birth attendants with the history of puerperal sepsis Journal of Science Foundation 2018;16(2):65-69